2013
DOI: 10.1007/s11136-013-0461-2
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and physical, mental, and cognitive disabilities among nursing home residents in Jordan

Abstract: This study revealed a substantial impact of physical, cognitive, and psychological disabilities on HRQOL of nursing home residents in Jordan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 28 publications
1
29
0
3
Order By: Relevance
“…31 Research and clinical practice have shown that cognitive impairment in itself influences mortality, functional impairment, and institutionalization, so if is likely that associations would have been even stronger for individuals with severe cognitive impairment. 32,33 Previous research has shown that functional decline and depression are predictors of all of the current study outcomes. 34,35 It might be thought that utility, derived from the EQ-5D, which is partly based on daily functioning and mood, would be associated irrevocably with these outcomes, but the associations between the individual domain scores and outcomes showed that problems in the anxiety and depression domain were not consistently associated with the outcomes.…”
Section: Functional Declinementioning
confidence: 88%
See 1 more Smart Citation
“…31 Research and clinical practice have shown that cognitive impairment in itself influences mortality, functional impairment, and institutionalization, so if is likely that associations would have been even stronger for individuals with severe cognitive impairment. 32,33 Previous research has shown that functional decline and depression are predictors of all of the current study outcomes. 34,35 It might be thought that utility, derived from the EQ-5D, which is partly based on daily functioning and mood, would be associated irrevocably with these outcomes, but the associations between the individual domain scores and outcomes showed that problems in the anxiety and depression domain were not consistently associated with the outcomes.…”
Section: Functional Declinementioning
confidence: 88%
“…Because individuals with a MMSE score less than 16 differed from the research population in a number of covariates (MMSE score, delirium, baseline ADL score, number of geriatric conditions), it is likely that their HRQOL at baseline would have been poorer . Research and clinical practice have shown that cognitive impairment in itself influences mortality, functional impairment, and institutionalization, so if is likely that associations would have been even stronger for individuals with severe cognitive impairment …”
Section: Discussionmentioning
confidence: 99%
“…In the elderly population, the emotional experiences and how they affect their levels of QoL have been a target of study in the context of the socioemotional selectivity theory (Carstensen et al, 2011;Carstensen, Isaacowitz, & Charles, 1999). However, the study of QoL among patients in nursing homes has not yet received the attention and resources it deserves (Almomani et al, 2014). Therefore, this paper attempted to explore the factors affecting the QoL levels in institutionalized older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Promoting quality of life (QoL) in older people is a special priority for those institutionalized (Almomani, McDowd, Bani-Issa, & Almomani, 2014), that is, those adults over 65 living in nursing homes. However, some controversy about QoL study is due to the lack of an agreed definition.…”
Section: Quality Of Life In Institutionalized Older Adultsmentioning
confidence: 99%
“…Pain can alter psychological status, causing higher levels of loneliness and depression and lower levels of happiness and life satisfaction . Pain hinders functional mobility and activities of daily living, and frail older adults consequently participate less in social activities, resulting in a deterioration of physical health and quality of life …”
mentioning
confidence: 99%